A wideband, 25/40dBm high I/O power GaN HEMT ultra-low noise amplifier using even-odd mode techniques. (October 2022) - Gupta, Manishankar Prasad; Gorre, Pradeep; Kumar, Sandeep; Nulu, Venugopal
Abstract: This paper presents a performance analysis of the low noise amplifier (LNA) for the first time using even-odd mode matching techniques in Gallium Nitride (GaN) HEMT Technology for marine communication. The proposed GaN LNA circuit consists of broadband stage I, main amplifier, and inverted broadband stage II, which provides a high input/output power, and ultra-low noise over wide bandwidth ranging from 0.5 GHz to 2.7 GHz with fractional impedance bandwidth of 138%. Broadband Stage I and Inverted broadband stage II are employed to provide input/output impedance matching transformation. The proposed LNA circuit with the incorporation of input/output broadband stages relax a 50Ω matching constraints and achieved high input and output power with good stability. The GaN HEMT LNA is analyzed and simulated using the RF simulator (ADS tool). The proposed GaN HEMT LNA is fabricated on RT Duroid substrate using Microwave Integrated Circuit (MIC) technology. The proposed LNA achieves a measured gain of 16 dB, while the simulated one is 17 dB with good insertion loss. An ultra-low noise figure of 0.6 dB flat is achieved over a wide bandwidth. In addition, the high output power is achieved 40dBm while input power is 25dBm which could overcome weak signal strength received by RF receiver for marine communication. A stability factor greater than one is achieved over a broad band ranging from 0.5 GHz to 2.7 GHz. The fabricated GaN HEMT LNA circuit has consumed power of 120 mW under a supply of 28 V. The area of the fabricated RF GaN HEMT LNA is 32 × 26 mm 2 .